A Cost Reimbursement Model for Hepatitis C Treatment Care Coordination. Issue 3 (May 2019) - Behrends, Czarina N.; Eggman, Ashley A.; Gutkind, Sarah; Bresnahan, Marie P.; Fluegge, Kyle; Laraque, Fabienne; Litwin, Alain H.; Meissner, Paul; Shukla, Shuchin J.; Perumalswami, Ponni V.; Weiss, Jeffrey; Wyatt, Brooke E.; et al.
Abstract : Objective: To estimate the cost of delivering a hepatitis C virus care coordination program at 2 New York City health care provider organizations and describe a potential payment model for these currently nonreimbursed services. Design: An economic evaluation of a hepatitis C care coordination program was conducted using micro-costing methods compared with macro-costing methods. A potential payment model was calculated for 3 phases: enrollment to treatment initiation, treatment initiation to treatment completion, and a bonus payment for laboratory evidence of successful treatment outcome (sustained viral response). Setting: Two New York City health care provider organizations. Participants: Care coordinators and peer educators delivering care coordination services were interviewed about time spent on service provision. De-identified individual-level data on study participant utilization of services were also used. Intervention: Project INSPIRE is an innovative hepatitis C care coordination program developed by the New York City Department of Health and Mental Hygiene. Main Outcome Measures: Average cost per participant per episode of care for 2 provider organizations and a proposed payment model. Results: The average cost per participant at 1 provider organization was $787 ($522 nonoverhead cost, $264 overhead) per episode of care (5.6 months) and $656 ($429 nonoverhead cost, $227 overhead, 5.7 months) at the other one. The first organization had a lower macro-costing estimate ($561 vs $787) whereas the other one had a higher macro-costing estimate ($775 vs $656). In the 3-phased payment model, phase 1 reimbursement would vary between the provider organizations from approximately $280 to $400, but reimbursement for both organizations would be approximately $220 for phase 2 and approximately $185 for phase 3. Conclusions: The cost of this 5.6-month care coordination intervention was less than $800 including overhead or less than $95 per month. A 3-phase payment model is proposed and requires further evaluation for implementation feasibility. Project INSPIRE's HCV care coordination program provides good value for a cost of less than $95 per participant per month. The payment model provides an incentive for successful cure of hepatitis C with a bonus payment; using the bonus payment to support HCV tele-mentoring expands HCV treatment capacity and empowers more primary care providers to treat their own patients with HCV. Abstract : Supplemental Digital Content is Available in the Text.